Designing Picture Books on Endemic Animals Based on SDGs Values To Foster Global Citizenship Character - Akhmad Fauzi; Ganjar Muhammad Ganeswara; Cik Suabuana; Susan Fitriasari; Dede Iswandi; Pratama Pramudya (Green Publisher Indonesia, 2024)
This study aims to design picture books on endemic animals based on Sustainable Development Goals (SDG) values to foster global citizenship character among junior high school students. Conducted at SMP Negeri 2 Pangenan and Bandung Independent School, the research involved 120 seventh-grade students in the Civics Education subject. Using the Research and Development (R&D) methodology, the study followed a systematic process of designing, developing, and validating the educational materials to ensure alignment with SDG values, particularly those promoting environmental sustainability and global responsibility. The findings indicate that the picture books not only engaged students effectively but also facilitated a deeper understanding of global citizenship through relatable local contexts. Students demonstrated an increased awareness of biodiversity and the importance of conserving endemic species as part of their civic responsibilities. The study contributes to educational literature by highlighting the potential of SDG-based picture books as impactful tools for character education, aligning with both national and international educational goals. This research offers a model for integrating global issues into local curricula, promoting a more comprehensive approach to character development that aligns with global citizenship objectives. The outcomes suggest that such materials can be beneficial in other educational settings to cultivate an appreciation for environmental stewardship and global interconnectedness among young learners.